Exploring the missional capacity of cathedral installations and events: theory and data - Francis, Leslie J. (Theology, 2026)
Hosting income-generating installations and events in cathedrals remains controversial. This article examines three narratives suggesting that such activities are missional and supportive of Anglican ecclesiology. Then it explores new survey data gathered from people attending the 2024 pre-Christmas son et lumière in Liverpool Cathedral. Five statistics stand out within these data: while only 30% were churchgoers (attending at least six times a year), 91% felt welcomed and at home in the cathedral, 61% lit a votive candle, and 56% said they would attend more events like this. As a consequence of attending this installation, 28% said that they were more likely to attend a carol service in the cathedral, and 21% that they were more likely to attend a carol service in their local church.